Ichthyofaunal Diversity of Dol net fishery at Navabandar, Gujarat - Sikotaria, K. M.; Temkar, G. S.; Azeez, P. Abdul; Mathew, K. L. (International Journal of Bio-resource and Stress Management, 2018)
Dolnetters contributed significantly to the fish production in Gujarat. However, dol net fishermen usually live in poverty threshold. Available secondary data suggests that overfishing prevails in Indian marine sector. While considering the complexity of dol net operations and the importance of fishery along North West coast of India present study done along one of the major dol net landing center of Gujarat. Study conducted to estimate the commercially important ictyofaunal diversity landed along Navabandar coast, Gujarat during the period from 15th August 2012 to 31st April 2013 (one fishing season). The present study revealed that altogether 24 major fish and shellfish species caught by dol net along Navabandar coast. There were 312 dolnetters in Navabandar fishing village. There was good variety of marine resource landing observed in dol net fishery. Non-penaeid shrimps contributed 40.22% of the total landings, followed by Harpadon nehereus (Bombay duck; 15%). Amongst the landed species, six were pelagic while 16 were demersal and the remaining two were miscellaneous (Non-penaeid shrimps). Demersal fishes contributed maximum (66%) to the total catch with contribution of about 72% to the total revenue. Sciaenids and pomfrets were the major as economically important species. Jaw fish fetched the maximum revenue (32%). Therefore, present study concluded that dol net fishery supported considerable variation in species composition. Study also revealed that due to usage of small mesh size there was sign of overfishing reported, so management policies must need to implement for conservation of marine fisheries resources for fulfilling present and future needs.